Lokale opfattelser af den kvindelige krop og dens reproduktive rolle. Et eksempel fra Uganda - Neema, Stella (Tidsskriftet Antropologi, 2019)
The paper deals with Banyankole women of Southwestem Uganda and examines their perceptions of the female body and its reproductive processes. Data is based on qualitative ethnographic studies carried out for a period of one year in 1992 in Southwestem Uganda. The Kinyankole interpretation of the female body is seen in the framework of the biosocial body, both as a physical and a social body with norms and core values of society to be adhered to for protection against all natural and supernatural forces. The intemal structure is likened to the outside structure of the body, hence the ideas of “intemal breasts” feeding the fetus and “intemal oils” that have to cleansed out, just as the extemal body needs cleaning. Further, the author describes the Banyankole understanding of the growth of the fetus in stages of metamorphosis ending with childbirth as a process of “authentic cooking”. Local perceptions of the female body during pregnancy and childbirth shape women’s expectations, practices, and the resultant obstetrical care choices they opt for, and it is related to their own understanding of risk which might deviate from the biomedical concepts of risk during pregnancy and childbirth.